Environmental information disclosure: a cross-country analysis from European Union public companies - Janicka, Małgorzata; Sajnóg, Artur (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
One of the contemporary challenges related to climate change and effectively managing raw materials is to reduce resource consumption and the negative environmental impact while simultaneously increasing the economy’s competitiveness. This requires that business entities change priorities and move to a sustainable relationship focused on ecological, economic and social well-being. Due to the transnational and global nature of the climate and the environment, actions in this area should be carried out at a supranational level. In European Union (EU) countries, successive directives are implemented regarding environmental changes and the taxonomy for non-financial reporting. This forces public companies, as large public interest units, to produce adequate quality data reporting in the ESG (Environmental, Social and Governance) area, including the environmental (E) indicator and its components. The article’s purpose is to make a comparative assessment of the current situation and to consider the prospects for environmental data disclosure by public companies listed on the regulated markets of the EU, with particular emphasis on energy consumption, water, waste production, and CO2 emissions. The Refinitiv database was used to test the quality of the environmental indicators. Public companies listed on the leading stock markets in the 27 EU Member States were included. The research period covers 2012–2021. We focus on checking how many companies report environmental data in any given year, and those that present them for at least one year, or for three, five, or ten years. The findings support the clear advantage of the quality of environmental data disclosure in the ‘old’ EU Member States (which joined before 2004) compared to the ‘new’ EU Member States. However, reporting on key environmental issues (water and energy consumption, waste production, and carbon dioxide) is very incomplete.